Norepinephrine is More Effective Than Midodrine/Octreotide in Patients With Hepatorenal Syndrome-Acute Kidney Injury: A Randomized Controlled Trial - El-Desoki Mahmoud, Eman Ibrahim; Abdelaziz, Doaa H; Abd-Elsalam, Sherief; Mansour, Noha O. (Frontiers in Pharmacology, 2021)
Background Terlipressin is the first-line pharmacological treatment for hepatorenal syndrome. When terlipressin is unavailable, midodrine /octreotide or norepinephrine, with albumin, represent the alternative treatments. The comparative efficacy of these alternative regimens remains unclear. Objective To compare the efficacy of midodrine/octreotide versus norepinephrine for the treatment of patients with hepatorenal syndrome. Methods In the intensive care setting, sixty patients with hepatorenal syndrome were randomized to initially receive either norepinephrine 0.5 mg / hour (Maximum 3 mg / hour) or oral midodrine 5 mg three times/day (Maximum 12.5 mg three times/day) plus octreotide 100 μg / 6 hour as subcutaneous injection (Maximum 200 μg / 6 hour), together with albumin (20 to 40 g/day). Treatment was allowed to a maximum of 10 days. Survival was analyzed for up to 30 days. The primary efficacy outcome was the proportion of patients achieved full response defined as return of serum creatinine to a value within 0.3 mg/dl of the baseline at the end of treatment. Results There was a significantly higher rate of full response in the norepinephrine group (15/26, 57.60%) compared to the midodrine/ octreotide group (5/25, 20%) (P = 0.006). Eleven (42.30 %) patients in norepinephrine group and 6 (24 %) in midodrine/ octreotide group survived (P = 0.166). Conclusion Norepinephrine plus albumin is significantly more effective than midodrine and octreotide plus albumin in improving renal function in patients with hepatorenal syndrome. (ClinicalTrials.gov Identifier: NCT03455322). https://clinicaltrials.gov/ct2/show/NCT03455322?cond=Hepatorenal+Syndrome&cntry=EG&draw=2&rank=1